RANCANG BANGUN APLIKASI RESERVASI SEWA MOBIL BERBASIS WEB - Permana, Andhika Solihan Asbi Adimart; Budiman (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Mekarsari Awet Ayu is a car rental service provider, specializing in Elf cars, which still uses a manual system for reservations and data recording. This causes various problems, such as recording errors, limited access to information, and difficulty in monitoring vehicle availability. This study aims to design and develop a web-based car rental reservation information system that can facilitate customers in making reservations and assist the company in data management. This system was designed using the PHP programming language, MySQL as the database, and the System Development Life Cycle (SDLC) software development method. The results of the implementation show that the developed system is capable of facilitating the reservation process, displaying real-time vehicle availability information, and improving the company's operational efficiency.